Infestation of Magulacra nigripennata Dognin (Lepidoptera: Cossidae) in a commercial cupuassu plantation in Nova Califórnia, Rondônia State, Brazil - Santos, Rodrigo Souza; Kamel de Oliveira, Tadário; Oliveira, Giordano Bruno da Silva; Macedo, Taysa Faltz (EntomoBrasilis, 2020)
The cupuassu (Theobroma grandiflorum (Willd ex Sprengel) K. Schum.) is a native tree from the tropical rainforest and one of the most important fruit trees in the Amazon region. Its pulp and seeds are widely used in the alimentary industry, as well as food by the people of northern Brazil. Among the factors that can compromise the production of cupuassu are the attack of diseases and insect pests. The aim of this work is to report the attack of a wood-borer lepidopteran in commercial cupuassu plantation located in the district of Nova Califórnia, Rondônia State, Brazil. In April 2019 an infestation of a wood-borer insect was observed causing the death of branches. Branches containing caterpillars in their inside were collected and taken to the Entomology Laboratory of the Embrapa Acre, where they were placed in a screened cage. After about 60 days, an adult insect emerged, which was identified as Magulacra nigripennata, a lepidopteran associated with cocoa and cupuassu plantations in that country. A random survey of 100 plants in the plantation area detected an infestation level of 36%, indicating the harmful potential of this pest to the cupuassu crops in the Amazon region.